2014
DOI: 10.1001/jama.2014.5616
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Structured Physical Activity on Prevention of Major Mobility Disability in Older Adults

Abstract: SUMMARY Importance In older adults reduced mobility is common and is an independent risk factor for morbidity, hospitalization, disability, and mortality. Limited evidence suggests that physical activity may help prevent mobility disability; however, there are no definitive clinical trials examining if physical activity prevents or delays mobility disability. Objective To test the hypothesis that a long-term structured physical activity program is more effective than a health education program (also referre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

54
1,100
4
27

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 1,174 publications
(1,185 citation statements)
references
References 28 publications
54
1,100
4
27
Order By: Relevance
“…While considerable effort has been directed toward understanding and attenuating age-related functional decline of the lower extremity [5][6][7][8][9], the relationship between aging and functional decline of the upper extremity has received relatively less attention.…”
Section: Introductionmentioning
confidence: 99%
“…While considerable effort has been directed toward understanding and attenuating age-related functional decline of the lower extremity [5][6][7][8][9], the relationship between aging and functional decline of the upper extremity has received relatively less attention.…”
Section: Introductionmentioning
confidence: 99%
“…In 2012, Stenholm et al reported that lifestyle (e.g., education, leisure time and work-related physical activity, smoking behavior, alcohol consumption), and physical health (e.g., chronic conditions such as hypertension, coronary heart disease, cardiovascular disease, or diabetes mellitus) earlier in life determine the rate of muscle strength decline (measured as handgrip strength) in old age (Stenholm et al 2012). Furthermore, various studies have evidenced that nutritional supplementation-such as vitamin D or protein intake-and exercise interventions can have a beneficial effect on muscle strength and physical performance, even in older populations (Bonnefoy et al 2003;Binder et al 2005;Chale-Rush et al 2010;Pahor et al 2014;Cesari et al 2015). In 2015, Sahni et al found a significantly higher leg lean mass in both males (n = 1166, age 60.2 ± 9.3 years) and females (n = 1509, age 59.0 ± 9.3 years) in the highest quartile of total protein and animal protein intake compared with those in the lowest quartiles (Sahni et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Это подтверждают данные M. Pahor и соавт., полученные из рандомизированного иссле-дования влияния программ ФА на хронические забо-левания и трудоспособность у пожилых [16]. На фоне регулярных физических упражнений и проведения образовательных программ обострение хронических заболеваний отмечали лишь в 14,7 % случаев по срав-нению с 19,8 % в другой группе -без ФА (р = 0,006), а уменьшение случаев нетрудоспособности -в 30,1 % случаев (против 35,5 % во 2-й группе, р = 0,03) [16]. Кроме того, еще одно кросс-секционное исследова-ние, завершившееся в 2010 г., доказало, что чем рань-ше человек начинает заниматься регулярно, тем меньше у него вероятность снижения когнитивной функции в пожилом возрасте (табл.…”
Section: риски недостаточной физической активностиunclassified